Effect of sewage sludge on the production and nutrition of red angico (Parapiptadenia rigida (Benth.) Brenan) seedlings - Santos, Rafael Pires dos; Costa, Alice Lemos; Pedroso, Lana Dorneles; Travessas, Amanda Oliveira; Vestena, Silvane (Revista Ecologia e Nutrição Florestal - ENFLO, 2019)
The objective of this study was to evaluate the effect of different substrates, containing sewage sludge, on macro and micronutrients content in plant tissues (root and shoot) of Parapiptadenia rigida (Benth.) Brenan seedlings. The treatments were: T1 (50% commercial substrate Plantmax® + 50% equine bed (organic compost), T2 (20% sewage sludge + 80% organic compost), T3 (40% sewage sludge + 60% organic compost) and T4 (60% sewage sludge + 40% organic compost). From 180 days since sowing the biometric characteristics were measured: shoot height, shoot diameter, shoot dry weight and root density, also the Dickson´s quality index. It was determined the contents of macro and micronutrients in the root system and in the aerial part of the cultivated seedlings. It was observed that the increasing order of the total content of the macronutrients evaluated in the root system was N > K > Mg > Ca > P > S and in the aerial part Ca > N > K > P > Mg > S; for the micronutrients, the content in both the root and shoot systems was Fe > Zn > Mn > B > Cu. The use of sewage sludge as substrate provided better nutritional quality seedlings with better growth and increase of aerial and root biomass.